Bringing the colour senses of personal photos to everyday living environment: the design and deployment of a tangible interactive lighting artifact. Issue 2 (2nd April 2020) - Noh, Boram; Jang, Sangsu; Kim, Kyungjin; Park, Young-Woo
ABSTRACT: The colour of a photo helps to visually communicate with us at an emotional level and remember the mood of the moment. We designed LightPalette to reinstate the direct reflex toward colour in personal photos through a tangible lighting artifact within the users' everyday environment. LightPalette works by retrieving major colours from a photo in smartphones and expresses them into the light on the acrylic shade enabling tangible adjustment of colours. We deployed LightPalette in 10 participants' homes for a week to investigate how they interpret the mood of a photo by expressing its colours through a lamp. Findings showed that LightPalette supported users in visualizing the invisible atmosphere of each moment and discovered its potential to be used as a colour diary for reflecting on the day. Our findings imply possibilities for future lighting that provides self-perception by portraying personal visual records stored in digital space into the lighting.